PERILAKU EKONOMI RUMAH TANGGA NELAYAN SEROK DI NEGERI HATIVE BESAR KOTA AMBON - Yoisye Lopulalan; Dionisius Bawole; Yolanda MTN Apituley; Christiani KP Kayadoe (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Potential of small pelagic fishery is abundant in Ambon City waters can be seen as an opportunity to improve the welfare of fisherman community, especially traditional fisherman such as serok fisherman in Hative Besar. Economic behavior or pattern of household decision making is needed to understand various efforts in improving the welfare of fishermen household. This study aims to (1) identify productive activities in fisheries sector and non-fishery sector by serok fisherman household in Hative Besar, (2) to describe the behavior of serok fisherman household decision making that acts as a producer, distributor and consumers, and (3) to describe the involvement of serok fisherman household in an effort to reduce poverty. The research method used is survey research method. The sample is determined by using purposive sampling technique. Data analysis was done descriptively qualitative. The results showed that serok fisherman household have productive activities within and outside the fishery sector as an attempt to generate family income. The economic behavior of serok fisherman household as producers, distributors and consumers is done in order to generate income and meet household needs. The involvement of serok fisherman household in reducing poverty is seen from some actions through the role of family members, job diversification and social networking.